Correction: Synthesis, characterization, and in vitro–in ovo toxicological screening of silibinin fatty acids conjugates as prodrugs with potential biomedical applications - Cristina Dehelean; Simona Cinta Pinzaru; Adrian Pirnau; Vasile Chis; Andrea Simion; Geza Lazar; Andrada Iftode; Iasmina Marcovici; Ersilia Alexa; Estera Boeriu (Biomolecules & Biomedicine)
Corrected article:  https://www.bjbms.org/ojs/index.php/bjbms/article/view/10600